Tantangan perpustakaan Universitas Islam Negeri Sumatera Utara menuju perpustakaan riset - Umi Kalsum (UIN Sumatera Utara, 2017)
This article discusses about the Challenge library of Islamic university north sumatera to the research library. The UIN-SU library's challenge to the research library is not an easy task because it takes a competent librarian, library collections such as books, articles, e-journals, e-books and scientific papers. This user behavior is more viewed as information needs. Accessing information today is easier, with the help of smart mobile phone, ipad, tablet, or computer we can access the information.Keywords: Challenge, Research, Library